Level of nutrition knowledge and its association with fat consumption among college students. - Yahia, Najat.; Brown, Carrie A.; Rapley, Melyssa.; Chung, Mei. (2016)
Background: Intake of saturated fat, trans fat, and cholesterol has been associated with increased risk of coronary heart disease. The aim of this study was to explore whether increased nutrition knowledge is associated with a reduction in the consumption of unhealthy fats in a sample of university students.; Keywords: Nutrition education, Fat consumption, Nutritional knowledge, University students.; Springer Open.